Measuring the Masses: Guidelines for Publication of Case Reports on Mass Gatherings. Issue Volume 34:Issue s1(2019) (May 2019) - Turris, Sheila; Rabb, Haddon; Callaghan, Christopher; Munn, Matthew Brendan; Ranse, Jamie; Lund, Adam; Chasmar, Elizabeth
Abstract : Introduction: The science supporting event medicine is growing rapidly. In order to improve the ability of researchers to access event data and improve the quality of publishing mass gathering cases, it would be of benefit to standardize event reports to permit the comparison of similar events across local and national boundaries. These data would support the development of practice standards across settings. Aim: The authors propose the creation of a publication guideline to support authors seeking to publish in this field. Method: Derivation study via analysis of published case reports using the Delphi process. Results: Data elements were inconsistently reported within published case reports. Categories of variables included: event demographics (descriptors of date, time, genre, activity, risks), attendance and population demographics, data related to climate and weather conditions, composition and deployment of an onsite medical team, highest level of care available onsite, patient demographics, patient presentations and measures of impact on the local health care system such as transfer to hospital rates. Of note, there was a high incidence of "missing" variables that would be of central interest to researchers. Discussion: Approaches to standardizing the collection and reporting of data are often discussed in the health care literature. The benefits of consistent, structured data collection are well understood. In the context of mass gathering event case reporting, the time is ripe for the introduction of a guideline (with accompanying guidance notes and dictionary). The proposed guideline requires the input of subject matter experts (in progress) to enhances its relevance and uptake. This work is timely as there is ongoing work on improving an international event medicine registry. If the evolution of both proceeds in lockstep, there is a good chance that access to a rigorous data set will become a reality.